2018
DOI: 10.1038/s41598-018-27965-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diabetes and antidiabetic medications on the risk of pancreatic cancer: a nationwide population-based study in Korea

Abstract: This study investigated the effects of diabetes and antidiabetic medications on the risk of pancreatic cancer(PaC). We extracted data on Koreans with newly diagnosed diabetes and selected age- and sex-matched controls provided by the National Health Insurance Corporation. Incident PaC was defined as a new registration in the Korea Central Cancer Registry under ICD-10 C25 with admission history until 2015. During 19,429,617.1 person-years, 8,589 PaCs were identified in 1,005,409 subjects for diabetes group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 28 publications
0
45
2
10
Order By: Relevance
“…A similar risk of PDAC is also reported with use of sulfonylureas (insulin secretagogues) routinely used in DM treatment [13, 5, 6]. Recently, these observations seem to be confirmed by Lee et al , who analyzed a Korean population-based cohort of subjects with and without DM and reported that risk of PDAC increases in patients after initiating therapy with sulfonylureas (HR, 1.73) and insulin (HR, 2.86) compared to no drug exposure group [17]. Some have speculated a direct causal relationship between insulin and PDAC occurrence secondary to anabolic effect of insulin on tumor cells [18].…”
Section: Insulin Use and Risk Of Pdacmentioning
confidence: 82%
“…A similar risk of PDAC is also reported with use of sulfonylureas (insulin secretagogues) routinely used in DM treatment [13, 5, 6]. Recently, these observations seem to be confirmed by Lee et al , who analyzed a Korean population-based cohort of subjects with and without DM and reported that risk of PDAC increases in patients after initiating therapy with sulfonylureas (HR, 1.73) and insulin (HR, 2.86) compared to no drug exposure group [17]. Some have speculated a direct causal relationship between insulin and PDAC occurrence secondary to anabolic effect of insulin on tumor cells [18].…”
Section: Insulin Use and Risk Of Pdacmentioning
confidence: 82%
“…Unfortunately, even in this case, no definitive conclusions have as yet been reached. It is not entirely clear whether, how much, and in which direction diabetes treatments affect the association between diabetes and PDAC [ 23 , 25 , 64 , 65 , 66 , 67 ]. To give a couple of examples, the protection provided by metformin, the most commonly drug used to treat T2DM, is currently under vigorous discussion, together with its mechanistic implications [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and even the increased risk of PDAC observed in insulin-treated patients in some case-control studies [ 27 , 74 ] can be misleading [ 26 , 72 ].…”
Section: Relationship Between Diabetes and Pancreatic Cancermentioning
confidence: 99%
“…In 2018, a population-based study was performed to evaluate the effects of T2DM and antidiabetic medications on the risk of PC by Lee D Y et al93 It was shown that among antidiabetic medications, metformin was an independent association with a reduced risk for future PC (HR=0.86, 95% CI=0.77–0.96) and subjects with dual exposure history to metformin plus thiazolidinedione or metformin plus dipeptidyl peptidase-4 inhibitor had a lower risk of PC compared to metformin-only treated subjects, which implicated that metformin could decrease the risk of PC. Pusceddu S et al, made a study in 2018 to figure out the association between metformin use and PC 94.…”
Section: Relationship Between Drug Therapy For T2dm and Pcmentioning
confidence: 99%
“…In 2018, Lee D Y et al, undertook a population-based study to find out the effects of T2DM and antidiabetic medications on the risk of PC 93. It was concluded that among antidiabetic medications, insulin exposure was with an increased risk of PC (HR=2.86, 95% CI=1.43–5.74) compared to subjects with no drug exposure, which implicated that insulin could increase the risk of PC.…”
Section: Relationship Between Drug Therapy For T2dm and Pcmentioning
confidence: 99%